Perspectives of health workers engaging in task shifting to deliver health care in low-and-middle-income countries: a qualitative evidence synthesis - Karen Coales; Hannah Jennings; Saima Afaq; Aatik Arsh; Mujeeb Bhatti; Faraz Siddiqui; Najma Siddiqi (Taylor & Francis Group, 2023)
Background Low- and middle-income countries (LMICs) are experiencing growing demand for healthcare services yet face a persistent shortage in access to specialist health workers (SHWs). Task shifting is an approach used to address this gap in service provision. Specific healthcare tasks are shifted to other, larger cadres of non-specialist health workers (NSHWs), including lay health workers with SHWs potentially taking on supervisory roles. Previous studies demonstrate that task shifting is both clinically and economically effective, however the impact of task shifting on health workers (HWs) is not fully understood. Objective The aim of this synthesis is to generate new knowledge about what influences HWs perspectives of benefits and costs of engaging in task shifting. Methods A qualitative evidence synthesis (QES) of peer-reviewed literature using databases CINAHL, the Cochrane Database of Systematic Reviews, Psych INFO, MEDLINE, EMBASE, Epistimonikos, Web of Science (science and social science citation index), Scopus LILACS, the African Index Medicus and Google Scholar. Eligible studies were those that included qualitative data about HWs perspectives of task shifting in LMICs. Information from eligible studies was extracted into a Google Sheet, and the data gathered were analysed thematically. Results Fifty-four studies were included in the QES. Results were organised under three themes, 'the cultural environment in which task shifting is employed', 'access to resources for task shifting' and 'alignment with personal values and beliefs, self-efficacy and personal emotional resilience'. Conclusion This is the first review bringing together views about task shifting from the perspective of different cadres of HWs drawn from diverse healthcare, geographical and country settings in LMICs. Task shifting is a complex process which relies upon the active engagement of HWs. Taking into consideration factors that influence HWs perspectives, such as their personal characteristics, preparatory training, and ongoing access to resources, is important for informing how task shifted healthcare initiatives are designed and delivered to successfully widen access to healthcare in LMICs.